Fontes e modos de aplicação de boro na cultura do eucalipto (clone I144) - Celestrino, Thiago de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Cerrado soils present low levels of boron being common supplementation of this element through soil and foliar fertilization. Therefore, it is important to define how better mode of application and source for the successful development and productivity of eucalyptus, with possible cost savings. Thus, this study aimed to compare the effect of B sources with high and low solubility applied in soil and high solubility applied on leaf of Eucalyptus spp. The experiment was conducted at farm Renascença, located in Três Lagoas/MS with latitude 20 34 'S and longitude 51 50' W and altitude of approximately 305 m, in 02/2012 to 02/2014. It was used a randomized block design with six treatments and five replications arranged in a factorial scheme 2 x 3, being: 0 kg ha- 1 B, 1 kg ha- 1 B, using boric acid as source (high solubility, 17 % B) or 1 kg ha-1 B, using as source borogran (low solubility, 10 % B), applied at planting, with or without application of boric acid foliar at 0.5% in a volume of 250 Lha-1. With the omission of B foliar there was an increase in plant height in treatments with the application of boron at planting, differing from the control. However, both of these sources, regardless of the solubility, showed similar results. The two foliar applications of B were sufficient for getting an increase in plant height when compared to treatments without B application at planting. At 18 and 24 months after planting there was increased on B foliar content in treatments with foliar application. Applying B at planting, regardless of source, as well as foliar application, were sufficient to reduce the symptoms of B deficiency. Regarding the sources used at planting, dose of 1kg ha-1 B, showed similar results on plant height, DBH and volume of wood. However, borogran increased the conten of B in the soil after 24 months of planting, from 20 to 40 cm layer, which can be beneficial for crop over time

Os solos de Cerrado apresentam baixo teor de boro no solo, sendo comum a suplementação deste elemento através da adubação via solo e foliar. Portanto, é importante definir qual o melhor modo de aplicação e fonte de B para o bom desenvolvimento e produtividade do eucalipto, com menor custo possível. Assim, objetivou-se, com este trabalho, comparar o efeito de fontes de B com alta e baixa solubilidade na cultura do eucalipto, bem como a aplicação foliar do micronutriente. O experimento foi conduzido na Fazenda Renascença, localizada no município de Três Lagoas/MS, com latitude 20o 34’ S e longitude 51o 50’ O e altitude de aproximadamente 305 m, no período de 02/2012 a 02/2014. O delineamento experimental foi o de blocos casualizados com seis tratamentos e cinco repetições, dispostos em um esquema fatorial de 3 x 2, sendo: 0 kg ha-1 de B, 1 kg ha-1 de B utilizando como fonte o ácido bórico (alta solubilidade, 17% B) ou 1 kg ha-1 de B utilizando como fonte o borogran (baixa solubilidade, 10% B), aplicados no sulco de plantio, com ou sem aplicações de ácido bórico via foliar na dose de 0,5% de ácido bórico na calda com volume de 250 L ha-1. Com a omissão de B via foliar houve incremento em altura de plantas nos tratamentos que receberam a aplicação do micronutriente no plantio, diferindo significativamente da testemunha. Porém, ambas as fontes, independente da solubilidade, apresentaram resultados semelhantes. As duas aplicações de B via foliar foram suficientes para que houvesse incremento em altura de plantas, quando comparadas aos tratamentos que não receberam aplicação de B no plantio. Aos 18 e 24 meses após o plantio foi constatado aumento no teor foliar de B nos tratamentos que receberam aplicação foliar. A aplicação de B no plantio, independente da fonte utilizada, assim como aplicação foliar do elemento, foram suficientes para reduzir os sintomas de deficiência de B. Com relação às fontes ...
Keywords: Eucalipto; Boro; Solubilidade; Elementos traços na nutrição; Adubação; Boron